Friends - Heine, Helme (New York : Atheneum, 1982)
Three friends who love to be together come to the realization that sometimes it's just not possible.
"A Margaret K. McElderry book.".
Keywords: Animals -- Fiction; Friendship -- Fiction; Friendship -- Fiction; Animals -- Fiction; Animals -- Fiction; Friendship -- Fiction